Curcumin induces autophagic cell death in human thyroid cancer cells. (February 2022) - Zhang, Li; Xu, Shichen; Cheng, Xian; Wu, Jing; Wu, Liying; Wang, Yunping; Wang, Xiaowen; Bao, Jiandong; Yu, Huixin
Abstract: Curcumin, a polyphenolic compound, is a well-known anticancer agent, although its poor bioavailability remains a big concern. Recent studies suggest that autophagy-targeted therapy may be a useful adjunct treatment for patients with thyroid cancer. Curcumin acts as an autophagy inducer on many cancer cells. However, little is known about the exact role of curcumin on thyroid cancer cells. In the present study, curcumin significantly inhibited the growth of thyroid cancer cells. Autophagy was markedly induced by curcumin treatment as evidenced by an increase in LC3-II conversion, beclin-1 accumulation, p62 degradation as well as the increased formation of acidic vesicular organelles (AVOs). 3-MA, an autophagy inhibitor, partially rescued thyroid cancer cells from curcumin-induced cell death. Additionally, curcumin was found to exert selective cytotoxicity on thyroid cancer cells but not normal epithelial cells and acted as an autophagy inducer through activation of MAPK while inhibition of mTOR pathways. Hyperactivation of the AKT/mTOR axis was observed in the majority of PTC samples we tested, and thyroid cancer cell lines along with cancer tissue specimens sustained a low basal autophagic activity. Taken together, our results provide new evidence that inducing autophagic cell death may serve as a potential anti-cancer strategy to handle thyroid cancer. Graphical abstract: Unlabelled Image Highlights: Curcumin induced autophagic cell death in thyroid cancer cells. Curcumin induces autophagy through inhibiting AKT and activating MAPK pathways. Thyroid cancer tissue specimens show low basal levels of autophagic activity.